2000
DOI: 10.1095/biolreprod62.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of the Zona Pellucida of In Vitro-Produced Bovine Embryos: A Scanning Electron and Confocal Laser Scanning Microscopic Study1

Abstract: Structural aspects of the bovine zona pellucida (ZP) of in vitro-matured (IVM) oocytes and in vitro-produced (IVP) embryos were studied in two experiments to find a tentative explanation for the zona's barrier function against viral infection. In Experiment 1, the ultrastructure of the outer ZP surface was studied. The diameter (nm) and the number of the outer pores within an area of 5000 microm(2) of 10 IVM oocytes, 10 zygotes, 10 8-cell-stage embryos, and 10 morulae were evaluated by scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 25 publications
1
85
0
3
Order By: Relevance
“…ZP proteins have been implicated in specific sperm binding of species, the prevention of polyspermy, and embryo protection between fertilization and implantation (Dunbar et al, 1991;Lasiene et al, 2009;Gupta et al, 2012;Yonezawa, 2014). However, there is a risk that virus particles could be trapped in the layers of the ZP (Vanroose et al, 2000;Van Soom et al, 2010). Singh et al (1982) demonstrated that bovine embryos (from 16-cell to blastocyst stage) with intact ZP that had been exposed to BoHV-1 for 24 hours did not show embryonic infection; but the virus was recovered from most of these embryos even after extensive washing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZP proteins have been implicated in specific sperm binding of species, the prevention of polyspermy, and embryo protection between fertilization and implantation (Dunbar et al, 1991;Lasiene et al, 2009;Gupta et al, 2012;Yonezawa, 2014). However, there is a risk that virus particles could be trapped in the layers of the ZP (Vanroose et al, 2000;Van Soom et al, 2010). Singh et al (1982) demonstrated that bovine embryos (from 16-cell to blastocyst stage) with intact ZP that had been exposed to BoHV-1 for 24 hours did not show embryonic infection; but the virus was recovered from most of these embryos even after extensive washing.…”
Section: Discussionmentioning
confidence: 99%
“…Dubuc (1994) demonstrated that oocytes recovered from BoHV-1 infected cows could be matured and in vitro fertilized, resulting in transferable embryos; however, the ratio of morphologically normal transferable blastocysts was decreased. According to Vanroose et al (2000), the zone pellucida (ZP) can protect against viral infection. Nonetheless, there is a risk that viral particles may be trapped on the outer layers of the ZP.…”
Section: Introductionmentioning
confidence: 99%
“…The ZP is perforated by radial canaliculi containing the cytoplasmic processes of the corona cells and contacting the surface of the immature oocyte [23]. It should be stressed that these corona cell expansions are not at any time actively penetrating the ZP; the latter is built around these processes as well as around the short oocyte microvilli [24].…”
Section: Structurementioning
confidence: 99%
“…Effectively, although the ZP is permeable to a large spectrum of components [23,44], differential staining of the ZP layers was obtained by treatment en bloc of the oocytes with antibodies or lectins [19,45,46]. The diffusion of (immuno)cytochemical reactions must be easy in the spongy outer layer; it may be progressively hampered while the ZP is becoming a plugged filter or when reagents precipitate in the periphery [47,48].…”
Section: Is the Zp Texture Correlated To Its Local Chemical Composition?mentioning
confidence: 99%
“…Vanroose et al [62] concluded that the intact bovine ZP of IVM oocytes and IVF embryos is constructed in such a way that BVDV and BHV-1 should not be able to traverse the ZP and reach the embryonic cells. However, it appears that few small viruses like BVDV can be caught in the outer layers of the ZP and contaminate the embryo at hatching.…”
Section: In Vitro Produced Embryosmentioning
confidence: 99%